[S-A]Lkidón de quinua, para conformar un sistema ternario, en la estabilidad de una emulsión tipo pickering (2018)
The research group of Universidad América, Center for Bioprospecting in Chemical Engineering Applied to the Study of Biomolecules and Industry, has focused on the study of quinoa starch, seeking to define a ""pattern of use"". Giving origin and importance to this project with the initiative to obtain an emulsifying agent of cosmetic grade from quinoa starch, for which four fundamental stages must be carried out that guarantee the application of this surfactant in Pickering type emulsions. However, what is developed in this project does not include the acceptance nor the regulations for its use directly on human skin, nor does it ensure the properties that the obtained emulsion can provide. Initially, the extraction of the quinoa starch and its physicochemical characterization is carried out; then proceed to make a chemical modification that leads to the design and development of the first design of experiments where the concentration of the reagent Octenil succinate anhydride and the pH of the reaction is varied.